A Study on the Eigenmodes of the Ridge Waveguide - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
The finite element method is carried out to investigate eigenmodes established in the ridge waveguide. Structure of the waveguide is divided into the mesh of triangular element. To obtain consistent eigenmodes, the edges and nodes of a triangular element are shared with neighboring elements. The eigen equation reveal large dimensional matrix so that Arnoldi methods is applied to compress it. Krylov-Schur iteration method is used to make it Schur form. The eigenpairs are obtained from the column matrix of similarity transformation matrix of an iterative process and consist of electric fields and potentials. The results are schematically represented with the electric field, 3-dimensional electric potential and electric equipotential contour. The eigenmodes represented by the electric field and potential are compared with each other. And the precise mode type is determined through the space distribution of those spectra.